Cardiovascular risk factors in women and the role of sex hormones - S. V. Yureneva; V. B. Mychka; L. M. Ilyina; S. N. Tolstov (Кардиоваскулярная терапия и профилактика, 2011)
Despite certain success in the recent years, the problem of cardiovascular disease (CVD) in women remains one of the greatest challenges of the 21st century. Its social and economic burden will continue to increase, due to increasing proportion of older women in the population. Recently, cardiologists have been focusing on menopause as a specific CVD risk factor in women. At the same time, other conditions, also increasing CVD risk, such as certain pregnancy complications and premature menopause, have not received enough attention. Hormone replacement therapy (HRT) remains the first-line treatment and the most effective strategy in young women with estrogen deficiency and postmenopausal women with menopausal symptoms. HRT effectiveness and safety is based on its timely start, low dose, and individually appropriate combination of estrogens and progestins. Interdisciplinary approach is essential for early identification of high-risk women, since lifestyle modification recommendations, diagnostic procedures, and, if needed, an active therapeutic intervention could reduce future CVD incidence in these women.